Faktor yang Berhubungan dengan Kejadian Computer Vision Syndrome pada Karyawan Bank - Nopriadi Nopriadi; Yuharika Pratiwi; Emy Leonita; Erna Tresnanengsih (Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Computer Vision Syndrome (CVS) is a collection of compound eye symp-toms due to using a computer.According to the initial survey, more than three quarter officers of Bank RK in Pekanbaru who daily work usingcomputers experience CVS. This study aimed to determine factors associated with CVS. This type of study wasquantitative observational with cross-sectional design with amount of sample 117 respondents. Data analysisused was univariate, chi-square used for bivariate analysis and multiple logistic regression used for multivariateanalysis. Based on the chi-square analysis the results showed that Bank RK officers who experienced CVS complaintswere in the forms of tired and tense eyes at 54,3%, neck pain at 28,7%, shoulder pain at 27, 7%, headacheat 25,5%, blurred vision at 20,2%, seeing twins at 17%, watery eyes and difficulty to focus at 14,9%, back pain at11,7%, sore eyes, irritation pain at 5,3%. Variables related to CVS were vision distance (p=0.016), monitor position(p=0.011), lighting (p=0.001), working period (p=0.002), the length of work (p=0.000). Variables not relatedto CVS was age (p=0.561). Variable of the length of work with computers ≥4 hours a day was 9 times riskier ofcausing CVS in Bank RK officers. This study indicates that the most dominant factor influential to CVS is the lengthof work, while other factors that act as confounding that affect CVS are monitor position, the lighting of the workstation, the period of working with computer.